Cross-sectional experimental assessment of pain modulation as part of multidimensional profiling of people with cervicogenic headache: protocol for a feasibility study - Thomas Graven-Nielsen; Wim Dankaerts; Annina Schmid; Sarah Mingels; Marita Granitzer (BMJ Open, 2024)
Background An endogenous pain modulation profile, reflecting antinociceptive and pronociceptive mechanisms, may help to direct management by targeting the involved pain mechanism. For individuals with cervicogenic headache (CeH), the characteristics of such profiles were never investigated. However, the individual nature of experiencing pain demands profiling within a multidimensional framework including psychosocial lifestyle characteristics. The objective of the current protocol is to assess the pain modulation profile, which includes psychosocial lifestyle characteristics among people with CeH.Methods and analysis A protocol is described to map pain modulation profiles in people with CeH. A cross-sectional non-randomised experimental design will be used to assess feasibility of mapping these profiles. The pain modulation profile is composed based on results on the Depression, Anxiety, Stress Scale, Pittsburgh Sleep Quality Index, Headache Impact Test and on responses to temporal summation of pain (pinprick), conditioned pain modulation and widespread hyperalgesia (mechanical pressure pain threshold and cuff algometry). Primary analyses will report results relating to outcomes on feasibility. Secondary analyses will involve an analysis of proportions (%) of the different psychosocial lifestyle profiles and pain profiles.Ethics and dissemination Ethical approval was granted by the Ethics Committee Research UZ/KU Leuven (Registration number B3222024001434) on 30 May 2024. Results will be published in peer-reviewed journals, at scientific conferences and, through press releases. Protocol V.3. protocol date: 3 June 2024.